Al-Iltizam Al-Islami fi Asy-Syi‘R Al-‘Arabi fi Bilad Yorba Nigeria - Ibraheem, Lateef Onireti (UIN Maulana Malik Ibrahim Malang, 2018)
الالتزام قضية مهمة في مذهب الأدب الإسلامي، الأدب الذي يصوّر الخالق والكون والإنسان وفقا لتعاليم الإسلام وقيمه. فالأدب العربي في نيجيريا بصفة عامة وفي بلاد يوربا بصفة خاصة يجب أن يتصف بهذه الصفات، ولذلك درس هذا البحث أعمال شعراء بلاد يوربا، نيجيريا، من حيث الالتزام الإسلامي. توصل البحث إلى أن أكثر الشعراء اليورباويين التزموا بالإسلام تعاليمه وقيمه ومنهجه في أعمالهم الأدبية إلا أن بعضهم تجاوزوا حد الالتزام بالمبالغة والإفراط في المحبة وعدم الصدق في العاطفة وتجريح حق الغير وإيراد التشبيه بالمحرمات. إلا أن ذلك لم يبلغ مبلغا يخرجهم من حوزة الإسلام، ولا أدبهم من الأدب الإسلامي، بل جعلهم أدباء ملتزمين في بعض القصائد وغير ملتزمين في غيرها. فأعمال الأدباء اليورباويين شعرها ونثرها تحتاج إلى دراسة مفصلة على المنهج الإسلامي لتمام فهمها وتحقيق قيمتها وتقدير جهود المقتصدين من أصحابها وردّ جماح المنحرفين منهم عن غيّهم. Consistency is a vital aspect of the school of thought of Islamic literature, the brand of Literature which creatively presents the Creator, the Universe and Man in accordance with Islamic teachings and values. The aim of this research is to study the level of adherence of poets in Yorubaland to Islamic teachings and norms in their works. To achieve this, it selected four themes of Arabic poetry, eulogy, elegy, love and political poetry. It shows that most of Yoruba poets adhere strictly and consistent with the teaching of Islam in their works, while very few of them were not consistent. It was due to their involvement in exaggerations, false motivation, trampling on the right of others, and drawing analogies from forbidding things like alcohol. These aspects, however, does not stripe their works from being branded Islamic literature in any way, it only connotes that they only lack of consistency in their adherence to the teachings of Islam. The creative works of Yoruba literary figures need thorough research in order to be well understood, ascertain their worth, appreciate the consistent ones Islamically among them and guide the straying ones to the right path.